2022
DOI: 10.3389/fimmu.2022.1039241
|View full text |Cite
|
Sign up to set email alerts
|

ROS-triggered endothelial cell death mechanisms: Focus on pyroptosis, parthanatos, and ferroptosis

Abstract: The endothelium is a single layer of epithelium covering the surface of the vascular system, and it represents a physical barrier between the blood and vessel wall that plays an important role in maintaining intravascular homeostasis. However, endothelial dysfunction or endothelial cell death can cause vascular barrier disruption, vasoconstriction and diastolic dysfunction, vascular smooth muscle cell proliferation and migration, inflammatory responses, and thrombosis, which are closely associated with the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(89 citation statements)
references
References 142 publications
(198 reference statements)
0
52
0
1
Order By: Relevance
“…ROS has been found to play an important role in NLRP3 inflammasome activation [59][60][61]. Oxidative stress, as the upstream signal of NLRP3 inflammasome activation, can up-regulate the expression of NLRP3, procaspase-1, and ASC and promote the assembly of the NLRP3 inflammasome, which in turn causes pyroptosis [34]. Nrf-2 is an important redox transcription factor that can improve the oxidative stress status of the body and maintain the redox balance of cells by regulating the production of antioxidant enzymes [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS has been found to play an important role in NLRP3 inflammasome activation [59][60][61]. Oxidative stress, as the upstream signal of NLRP3 inflammasome activation, can up-regulate the expression of NLRP3, procaspase-1, and ASC and promote the assembly of the NLRP3 inflammasome, which in turn causes pyroptosis [34]. Nrf-2 is an important redox transcription factor that can improve the oxidative stress status of the body and maintain the redox balance of cells by regulating the production of antioxidant enzymes [62].…”
Section: Discussionmentioning
confidence: 99%
“…As the activation of inflammasomes and release of inflammatory factors are important in the process of pyroptosis and the fact that oxidative stress can cause pyroptosis [34], we measured the levels of serum IL-1β, IL-18, SOD, GSH and MDA. The results showed that administration of DOX increased the serum levels of IL-1β, IL-18, MDA and decreased the serum levels of SOD and GSH compared to that in the control group, while AS-IV treatment decreased serum IL-1β, IL-18, MDA and increased SOD and GSH levels (Fig.…”
Section: As-iv Attenuates Dox-induced Inflammation and Oxidative Stressmentioning
confidence: 99%
“…miR-30c decreases the production of reactive oxygen species (ROS) ( 51 , 52 ), which are key for tissue damage and myocardial protection. Furthermore, it is widely reported that overactivation of ROS pathway signaling increases pyroptosis ( 53 , 54 ). During MI/R injury, excessive production ROS and increased pyroptosis of cardiomyocytes may be induced by decreased expression of miR-30c.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen peroxide, superoxide anions, and hydroxyl radicals are the sources of the intracellular ROS production [ 80 ]. Zheng et al [ 81 ] systematically reviewed the sources of endothelial ROS production and their underlying mechanism on ECs death. Moreover, ROS also increases intracellular calcium concentration and activates proto-oncogenes and pro-inflammatory genes [ 82 ].…”
Section: Hydroxytyrosol In Oxidative Stress-induced Endothelial Dysfu...mentioning
confidence: 99%